Structural Characterization of Non-structural Protein 9 Complexed With Specific Nanobody Pinpoints Two Important Residues Involved in Porcine Reproductive and Respiratory Syndrome Virus Replication - Yan Wang; Rui Li; Songlin Qiao; Jiaxi Wang; Hongliang Liu; Zhijun Li; Hongfang Ma; Lei Yang; Haiyu Ruan; Maoyang Weng; Julian A. Hiscox; James P. Stewart; et al. (Frontiers in Microbiology, 2020)
Porcine reproductive and respiratory syndrome (PRRS), caused by PRRS virus (PRRSV), is a widespread viral disease that has led to huge economic losses for the global swine industry. Non-structural protein 9 (Nsp9) of PRRSV possesses essential RNA-dependent RNA polymerase (RdRp) activity for viral RNA replication. Our previous report showed that Nsp9-specific nanobody, Nb6, was able to inhibit PRRSV replication. In this study, recombinant Nsp9 and Nsp9-Nb6 complex were prepared then characterized using bio-layer interferometry (BLI) and dynamic light scattering (DLS) analyses that demonstrated high-affinity binding of Nb6 to Nsp9 to form a homogeneous complex. Small-angle X-ray scattering (SAXS) characterization analyses revealed that spatial interactions differed between Nsp9 and Nsp9-Nb6 complex molecular envelopes. Enzyme-linked immunosorbent assays (ELISAs) revealed key involvement of Nsp9 residues Ile588, Asp590, and Leu643 and Nb6 residues Tyr62, Trp105, and Pro107 in the Nsp9-Nb6 interaction. After reverse genetics-based techniques were employed to generate recombinant Nsp9 mutant viruses, virus replication efficiencies were assessed in MARC-145 cells. The results revealed impaired viral replication of recombinant viruses bearing I588A and L643A mutations as compared with replication of wild type virus, as evidenced by reduced negative-strand genomic RNA [(−) gRNA] synthesis and attenuated viral infection. Moreover, the isoleucine at position 588 of Nsp9 was conserved across PRRSV genotypes. In conclusion, structural analysis of the Nsp9-Nb6 complex revealed novel amino acid interactions involved in viral RNA replication that will be useful for guiding development of structure-based anti-PRRSV agents.